1999
DOI: 10.1007/bf03161770
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microhabitat variation on seedling recruitment ofChamaecyparis thyoides andAcer rubrum

Abstract: Chamaecyparis thyoides (Atlantic white-cedar) swamps are in decline in the New Jersey Pinelands, while Aeer rubrum (red maple) swamps are increasing. One possible reason for this occurrence may be differences in seedling recruitment of the two species. Seedling establishment of different species is expected to vary with physical conditions and requirements for safe sites. This study examined differences in seedling recruitment for C. thyoides and A. rubrum in the New Jersey Pinelands. A field survey of six C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
(28 reference statements)
1
14
1
Order By: Relevance
“…In fact, experimental seedlings grew at least as much, and for some growth measures more, on tussock sedge substrate than on moss-litter substrate and seedling survival was similar between substrates. The weak substrate type effect on experimental seedlings was not only in contrast to the previous survey (Gengarelly and Lee, in press) but also to other AWC studies that indicate AWC prefer peat soils for establishment (Korstian and Brush, 1931;Little, 1950;Allison and Ehrenfeld, 1999). Furthermore, seedling success on the two substrate types was inconsistent with the significant differences in soil moisture and pH between the substrates.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…In fact, experimental seedlings grew at least as much, and for some growth measures more, on tussock sedge substrate than on moss-litter substrate and seedling survival was similar between substrates. The weak substrate type effect on experimental seedlings was not only in contrast to the previous survey (Gengarelly and Lee, in press) but also to other AWC studies that indicate AWC prefer peat soils for establishment (Korstian and Brush, 1931;Little, 1950;Allison and Ehrenfeld, 1999). Furthermore, seedling success on the two substrate types was inconsistent with the significant differences in soil moisture and pH between the substrates.…”
Section: Discussioncontrasting
confidence: 68%
“…Other studies of AWC seedlings have also shown greater frequency of occurrence or growth in organic peat soils (histosols) with moss and litter substrate than on other substrates (Little, 1950;Laderman, 1989;Allison and Ehrenfeld, 1999), although Haas and Kuser (1999) found it was possible to establish AWC seedlings on a sandy mineral soil. These conflicting results reveal uncertainty in our understanding of AWC germination and seedling establishment requirements with regard to substrate.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Extant wetlands, in many ecoregions, represent remnants of increasingly endangered plant communities. For example, in the United States of America, the extensive wetprairie system in the Willamette Valley, OR (Noss et al 1995;Christensen et al 1996), the prairie pot-holes of the mid-west (Kantrud et al 1989;Galatowitsch and van der Valk 1994), the whitecedar forests of the Northeast (Zampella 1987;Schneider 1991, 1993;Allison and Ehrenfeld 1999), and the coastal marshes of southern California (Zedler 1991(Zedler , 1996 have all undergone major reductions in area compared to historical conditions.…”
Section: Introductionmentioning
confidence: 97%